Investigating the Mechanism of Germinal Center Shutdown - Arulraj, Theinmozhi; Binder, Sebastian C.; Meyer-Hermann, Michael (Frontiers in Immunology, 2022)
Germinal centers (GCs) are transient structures where affinity maturation of B cells gives rise to high affinity plasma and memory cells. The mechanism of GC shutdown is unclear, despite being an important phenomenon maintaining immune homeostasis. In this study, we used a mathematical model to identify mechanisms that can independently promote contraction of GCs leading to shutdown. Proposed mechanisms acted by primarily targeting various processes from antigen acquisition to terminal differentiation of B cells, and promoted GC contraction by ultimately decreasing the number of B cell divisions and recycling cells. Based on the in-silico predictions, we suggest a combination of experiments that can be potentially employed by future studies to unravel the mechanistic basis of GC shutdown.